The Double Binds of Ethics after the Holocaust
XIII, 183 p.
Keywords: The Double Binds of Ethics after the Holocaust advances the idea that the Holocaust undermined confidence in basic beliefs about human rights and shows steps of salvage and retrieval that need to be taken if ethics is to be a significant presence in a world still besieged by genocide and atrocity.